ANALISIS KIMIA DAN DESTILASI KERING KAYU KARET - Sri Komarayati; Dadang Setiawan; Tjutju Nurhayati (Jurnal Penelitian Hasil Hutan, 1995)
This paper  deals with chemical  and charcoal properties  of rubberwood.  The analysis of chemical  propertis comprises of  the determination   of cellulose, holocellulose,   lignin, pentosan, moisture  content,    ash  content,  silica  content,  solubility  in  cold  water,    hot  water,   sodium hydroxide  1  percent  and ethanol-benzene    (1 : 2). The  analysis of charcoal property comprises of charcoal,  tar,  pyroligneous  liquor,   calorific value,  volatile matter and fixed carbon.The result showed  that cellulose  content   48.38   %  -  50.26  %  ;  holocellulose 59.68   %  -60.17    %  ;  lignin 31.33  %  -  33.49  %  ;  pentosan  15.98   %  -  16.43   %  ;  moisture   content 7.34  -9. 98 %  ; ash 0. 64 - 0. 71  % ; silica 0. 57 %  - 0. 60 %.  Solubility in cold water 2. 39 %  - 4.48 %;  in hot water  3.33   %   - 5.93   %  ;  in alcohol-benzene     (1  :  2)  2.35  %   - 2.37    %  and in one percent sodium hydroxide 18. 87 %  - 20. 72 %.Based on chemical analysis,  especially  the cellulose and pentosan  content,   rubberwood is suitable as raw material forpulp and paper,  rayon andfiberwood.Chemical analysis of charcoal indicated that charcoal yield variedfrom 28.16  %  - 29. 77 %  ;  tar   6.86  %  -  7.4666   %  ; pyroligneous   liquor  87.50   -  103.23   %  ;  calorific value  7114.68  cal/gr -7166. 77 cal/gr .fixed carbon 73.82   %  -  78.05 %  and volatile mailer 20.45 % - 23. 61 %. Proximate  analysis  of charcoal  obtained from this  experiments   revealed that   the   quality are suitable for commercial charcoal, metallurgy charcoal and as raw malerial of activated charcoal.